2016
DOI: 10.1002/adma.201602580
|View full text |Cite
|
Sign up to set email alerts
|

Variable Stiffness Fiber with Self‐Healing Capability

Abstract: A variable stiffness fiber made of silicone and low melting point alloys quickly becomes >700 times softer and >400 times more deformable when heated above 62 °C. It shows remarkable self‐healing properties and can be clamped, knitted, and bonded, as shown in a foldable multi‐purpose drone, a wearable cast for bone injuries, and a soft multi‐directional actuator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
166
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(167 citation statements)
references
References 36 publications
1
166
0
Order By: Relevance
“…Compared to other classes of shape‐memory materials, shape‐memory polymers and composites are lightweight, inexpensive, can be made into parts using a variety of manufacturing technologies, and can have a broad range of properties . Thanks to these characteristics, they find applications in a variety of engineering areas including aerospace, wearable electronics, and biomedicine . The design of shape‐memory polymers is usually based on the combination of two distinct phases, a stable phase and a programmable phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other classes of shape‐memory materials, shape‐memory polymers and composites are lightweight, inexpensive, can be made into parts using a variety of manufacturing technologies, and can have a broad range of properties . Thanks to these characteristics, they find applications in a variety of engineering areas including aerospace, wearable electronics, and biomedicine . The design of shape‐memory polymers is usually based on the combination of two distinct phases, a stable phase and a programmable phase.…”
mentioning
confidence: 99%
“…[3] Thanks to these characteristics, they find applications in a variety of engineering areas including aerospace, [4] wearable electronics, [5] and biomedicine. [6] The design of shapememory polymers is usually based on the combination of two distinct phases, a stable phase and a programmable phase. The programmable phase can undergo a reversible stiffening transition triggered by an external stimulus, while the stable phase remains unaffected.…”
mentioning
confidence: 99%
“…[17] Replacing conventional electromagnetic clutches with custom designs tailored for wearable applications has helped in reducing size and weight of these components for unpowered exoskeletons. [22][23][24][25][26][27] However, several limitations are still present, such as the achieved blocking forces, the elongation ratio, and the low response time in the case of variable stiffness technologies. [14,[18][19][20] Electrostatic clutches, developed by flexible materials such as a polyethylene terephthalate film, demonstrate to be a promising soft robotics technology for the application in an unpowered ankle foot orthosis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tonazzini et al reported the use of paraffin wax to tune the stiffness of fibers. As the paraffin solidified, the stiffness of fibers increased . Meerbeek et al reported the morphing of liquid metal alloys and bicontinuous elastic foams by varying the stiffness induced by temperature.…”
Section: Introductionmentioning
confidence: 99%